ACCOUNTING INFORMATION SYSTEMS AND THEIR CONTRIBUTION TO THE IMPROVEMENT OF RETURN ON ASSETS AND OPERATING CASH FLOW TO DEBT RATIO: EVIDENCE FROM NATIONAL HOSPITALS OF THE UK - Jinan Abed Khaji; Ali Mohammed Alkndlee; Anmar Adnan Khudhair (Scholar Express Journals, 2025)
This research work investigates how accounting information systems enable the improvement of financial performance, focusing on the variables of ROA and the operating cash flow to debt ratio, in national hospitals within the UK. In today's world, with increased dependency on technology within the health care sector, AIS has become an essential tool for maintaining financial data and presenting more accurate reports to support strategic decisions. Drawing on a sample of 40 national hospitals during the 2011-2020 period, this paper examines the relationship between the effectiveness of AIS and improvement in asset utilization and debt management. The results suggest that AIS implementation is positively and highly significantly related to an increase in ROA, reflecting improved asset utilization and operational efficiency. This also proves that AIS significantly enhances the capacity of hospitals to manage their cash flows and debt obligations in a better way. Some challenges linked to debt management were identified in larger institutions or higher debt levels. The study established that AIS is crucial to achieving improved financial performance in national hospitals, while adopting additional financial strategies that would enhance the efficiency of AIS in debt management.
Keywords: Accounting Information Systems; Debt Management; Return on Assets